2017
DOI: 10.3389/fpsyg.2017.01755
|View full text |Cite
|
Sign up to set email alerts
|

When and Why Does Materialism Relate to Employees’ Attitudes and Well-being: The Mediational Role of Need Satisfaction and Need Frustration

Abstract: Materialistic values may be detrimental for people’s well-being. However, we know little about why (i.e., explaining mechanisms) and when (i.e., boundary conditions) this is the case. Although low satisfaction of the psychological needs is said to play a key role in this process, a recent meta-analysis indicates that the explaining power of need satisfaction is limited and suggests that need frustration may be more important. Moreover, although materialism may be detrimental in some life domains, studies in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 69 publications
5
43
0
2
Order By: Relevance
“…That is, a relatively high extrinsic goals pursuit of employees will produce and generate greater relationship conflicts when engaging in innovative activities. Previous studies just found that employees’ extrinsic and intrinsic goals could influence their job outcomes, such as job satisfaction and turnover intentions ( Vansteenkiste et al, 2007 ; Unanue et al, 2017 ). Our study suggest that employees’ goal pursuit is also an important factor that can moderate the relationships between innovative behaviors and its outcomes.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…That is, a relatively high extrinsic goals pursuit of employees will produce and generate greater relationship conflicts when engaging in innovative activities. Previous studies just found that employees’ extrinsic and intrinsic goals could influence their job outcomes, such as job satisfaction and turnover intentions ( Vansteenkiste et al, 2007 ; Unanue et al, 2017 ). Our study suggest that employees’ goal pursuit is also an important factor that can moderate the relationships between innovative behaviors and its outcomes.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…In a recent study, Unanue et al (2017bUnanue et al ( , p. 1755 showed the mediating roles of psychological needs satisfaction and frustration in the relationship between materialism and wellbeing. Applying this idea to the current results, we posit that a high-salary offer may satisfy the needs of materialists, a low-salary offer may frustrate the needs of materialists, and strong-brand offers may satisfy the needs of individuals with a high inclination for S-EB-R.…”
Section: Discussionmentioning
confidence: 97%
“…The satisfaction of only functional needs without delivering psychological benefits is not enough to feel emotionally connected with a brand. The needs satisfaction-frustration framework and results regarding the different impacts of needs satisfaction and frustration in predicting outcomes for well-being (Unanue et al, 2017b(Unanue et al, , p. 1755) deliver a valuable interpretation for results on anticipated job satisfaction as well. The preference for the SEBUAS job offer, even though it satisfies identity needs, may be extremely frustrating for materialists, and thus induce a strong affect and evaluative reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations